Experiencing loss : traumatic memory and nostalgic longing in Anne Landsman's The Devil's Chimney and The Rowing Lesson, and Rachel Zadok's Gem Squash Tokoloshe - Roux, Rowan Pieter (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2013)
This thesis examines the experience of loss in Anne Landsman's novels The Devil's Chimney (1997) and The Rowing Lesson (2008), and Rachel Zadok's Gem Squash Tokoloshe (2005). Positing the Truth and Reconciliation Commission (TRC) as an impetus for emerging literary traditions within contemporary South African fiction, the argument begins by evaluating the reasons for the TRC's widespread impact, and considers the role that the individual author may play within a culture which is undergoing dramatic socio-political upheavals. Through theoretical explication, close reading, and textual comparison, the argument initiates a dialogue between psychoanalysis and literary analysis, differentiating between two primary modes of experiencing loss, namely traumatic and nostalgic memory. Out of these sets of concerns, the thesis seeks to understand the inextricability of body, memory and landscape, and interrogates the deployment of these tropes within the contexts of traumatic and nostalgic loss, examining each author's nuanced invocation. A central tenet of the argument is a consideration, moreover, of how the dialogic imagination has shaped storytelling, and whether or not narrative may provide therapeutic affect for either author or reader. The study concludes with an interpretation of the changing shape of literary expression within South Africa.
Keywords: Landsman, Anne, 1959- -- The Devil's Chimney -- Criticism and interpretation; Landsman, Anne, 1959- -- The Rowing Lesson -- Criticism and interpretation; Zadok, Rachel -- Gem Squash Tokoloshe -- Criticism and interpretation; Zadok, Rachel -- Gem Squash Tokoloshe -- Criticism and interpretation; South Africa Truth and Reconciliation Commission; Psychic trauma in literature; Nostalgia in literature; Repression (Psychology) in literature; Literature, Modern -- 20th century -- History and criticism; Literature, Modern -- 21st century -- History and criticism; South Africa -- Race relations